MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI METODE BERMAIN MEDIA KARTU ANGKA PADA ANAK USIA 4-5 TAHUN DI TK MAYA PERMATA KECAMATAN KAMPAR KABUPATEN KAMPAR - Melda Wimar; Zulkifli Zulkifli; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase ability to recognize the concept of numbers 4-5 years oldof children through the method of playing the media card numbers in kindergarten Maya Permata District Kampar Regency Kampar . This study is the kinds of research a class action or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subjects are empirically 4-5 years old of children who are 20 children in kindergarten Maya Permata. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The results showed lower method of playing media card numbers can improve the ability to know the concept of numbers on a group of children. It can be seen from the increase in the average percentage of children recognize the concept Numbers on the first cycle of 59.16%, which is in the category fairly and increased by 29.94% in the second cycle to 76 , 87% of which are in both categories. Thus, the method of playing the media card numbers can improve the ability to know the concept of numbers of children age 4-5 years in kindergarten Maya Permata District Kampar Regency Kampar.Keywords : Ability To Recognize The Concept Of Numbers, Media Playing Cards Figures